Dietary supplementation of betain to improve the growth and feed utilization in hybrid grouper (Epinephelus lanceolatus♂ × Epinephelus fuscoguttatus♀) juvenile - Idul La Muhamad; Mia Setiawati; Wiyoto Wiyoto; Julie Ekasari (Jurnal Akuakultur Indonesia)
Betaine plays some important roles in feed utilization and fish metabolism. The aim of this study was to evaluate the effect of dietary betaine supplementation on the growth performance and feed utilizationin hybrid grouper (Epinephelus lanceolatus♂ × Epinephelus fuscoguttatus♀). A completely randomized experimental design with four dietary levels of betaine, i.e.0.0%, 0.5%, 1.0%, and 2.0% in quadruplicate was done.Hybrid grouper juvenile obtained from Brackishwater Aquaculture Development Center, Situbondo, with an initial body length and body weight of 5.89 ± 0.05 cm and 2.86 ± 0.09 g, respectively was used as the tested animal. The fish was maintained in 60 cm x 40 cm x 40 cm aquaria with 75 L working capacity with individual recirculating system with a fish density of 15 fish/aquarium for 50 days. Experimental diet was provided to apparent satiation twice a day. The results of this study demonstrated that dietary betaine at a level of 0.5% resulted in higher feed utilization efficiency, protein and methionine retentions, and growth performance and lower ammonia excretion than those of the control (P<0.05). Higher antioxidative status was indicated by the lower malondialdehyde (MDA) in the liver of fish fed with betaine supplemented diets at levels of 1 - 2%. In conclusion, betaine supplementation of 0.5% could increase feed utilization efficiency and growth performance of hybdrid grouper.